Analysis of the 30 October 2020 İzmir-Samos Tsunami Measurements with Compressive Sensing Method - Alan, Ali Rıza; Bayındır, Cihan (Fırat University, 2024)
Although they do not occur as frequently as other natural disasters, tsunamis can cause tremendous damage to the near-shore ecosystem. On October 30, 2020, at 12:51 p.m. an earthquake with a magnitude of 6.9 Mw occurred at UTC (2:51 p.m. GMT+03:00). The epicenter of the earthquake is located off the Greek island of Samos, approximately 23 km south of Turkey’s İzmir province. This earthquake caused the İzmir-Samos (Aegean) tsunami, which has the same name, on October 30, 2020. In this research, the efficient reconstruction of the hydrodynamic time series of this tsunami with efficient measurements was examined using the Compressive Sensing (CS) algorithm, which is an effective detection technique applied to observational data. For this purpose, tsunami time series records obtained from Kos Marina and Bodrum stations of the UNESCO data portal were used. The potential application of effectively measuring and reconstructing tsunami water surface fluctuation time series and the Fourier spectra of these series with the CS algorithm has been investigated. It has been shown that tsunami parameters such as water surface fluctuations, horizontal and vertical tsunami velocities, and tsunami flood discharge time series can be successfully measured, analyzed, and recorded using CS. In addition, potential future directions and the usefulness and applicability of our findings are also examined.

Diğer doğal afetler kadar sık meydana gelmeseler de tsunamiler kıyıya yakın ekosisteme çok büyük zararlar verebilir. 30 Ekim 2020’de saat 12:51 p.m. UTC’de (2:51 p.m. GMT+03:00) 6,9 Mw büyüklüğünde bir deprem meydana gelmiştir. Depremin merkez üssü, Türkiye’nin İzmir ilinin yaklaşık 23 km güneyinde, Yunanistan’ın Samos adası açıklarında bulunmaktadır. Bu deprem 30 Ekim 2020’de kendisiyle aynı adı taşıyan İzmir-Samos (Ege) tsunamisine neden olmuştur. Bu araştırmada, gözlemsel verilere uygulanan etkili bir algılama tekniği olan Sıkıştırılabilir Algılama (CS) algoritması kullanılarak bu tsunaminin hidrodinamik zaman serilerinin verimli ölçümlerle geri çatılması incelenmiştir. Bu amaçla UNESCO veri portalının Kos Marina ve Bodrum istasyonlarından elde edilen tsunami zaman serisi kayıtlarından faydalanılmıştır. Tsunami su salınım seviyesi zaman serilerinin ve bu serilerin Fourier spektrumlarının CS algoritmasıyla etkili bir şekilde ölçülerek geri çatılmasının potansiyel uygulaması araştırılmıştır. CS kullanılarak su seviyesi salınımı, yatay ve düşey tsunami hızları, tsunami taşkın debisi zaman serileri gibi tsunami parametrelerinin başarıyla ölçülebileceği, analiz edilebileceği ve kayıt altına alınabileceği gösterilmiştir. Ayrıca gelecekteki potansiyel yönelimler, bulgularımızın kullanışlılığı ve uygulanabilirliği de irdelenmiştir.
30 Ekim 2020 İzmir-Samos Tsunamisi Ölçümlerinin Sıkıştırılabilir Algılama Yöntemiyle Analizi
Keywords: Coastal Sciences and Engineering; Kıyı Bilimleri ve Mühendisliği